Nutritional Keys for Intestinal Barrier Modulation - De Santis, Stefania; Cavalcanti, Elisabetta; Mastronardi, Mauro; Jirillo, Emilio; Chieppa, Marcello (Frontiers in Immunology, 2015)
The intestinal tract represents the largest interface between the external environment and the human body. Nutrient uptake mostly happens in the intestinal tract, where the epithelial surface is constantly exposed to dietary antigens. Since inflammatory response towards these antigens may be deleterious for the host, a plethora of protective mechanisms take places to avoid or attenuate local damage. For instance, the intestinal barrier is able to elicit a dynamic response that either promotes or impairs luminal antigens adhesion and crossing. Regulation of intestinal barrier is crucial to control intestinal permeability whose increase is associated to chronic inflammatory conditions. The cross talk among bacteria, immune and dietary factors is able to modulate the mucosal barrier function, as well as the intestinal permeability. Several nutritional products have recently been proposed as regulators of the epithelial barrier, even if their effects are in part contradictory. At the same time, the metabolic function of the microbiota generates new products with different effects based on the dietary content. Besides conventional treatments, novel therapies based on complementary nutrients is now growing. It has been recently used a fecal therapy approach for the clinical treatment of refractory Clostridium difficile infection instead of the classical antibiotic therapy. In the present review we will outline the epithelial response to nutritional components derived from diet intake and microbial fermentation focusing on the consequent effects on the epithelial barrier integrity.